Identification of the brain hemispheric dominance of UiTM students using EEG / Ahmad Faris Junaidi - Junaidi, Ahmad Faris (2006)
The purpose of this study is to identify the brain hemispheric dominance of UiTM students using EEG. It is a study that will compare the usage of the brain used by students from different field of study background. The study has been made on students from the electrical engineering faculty (FKE) of UiTM Shah Alam and also on the students from the faculty of technology creative and artistic (TEKA) of UiTM in Puncak Pcrdana. Entirely, there are 30 samples all together, 15 of them are from the electrical engineering faculty and the other 15 are from the technology creative and artistic faculty. The comparison between these two faculties was made on the overall maximum value of both hemispheric side of the brain, the BETA maximum value and also on the results obtained from the questionnaire. To acquire the EEG data from the samples, a three minute EEG data reading on the brainwave needs to be done on each sample. In conclusion to this study, from the obtained results, it is evidently that students from engineering background has a dominance of the left hemisphere of the brain and students from the arts background has a dominance of the right hemisphere of the brain.